THE LEGAL ISSUES IMPACT ON THE E COMMERCE - Johar; MGM; shukri, Sakinah mohd; Ferdous (International Journal of Psychosocial Rehabilitation, 2020)
This study investigate the legal issues impact on the E-commerce in Malaysia. Based on a finding, 34% of mobile phone owners have received unwanted Short Message Service (SMS) regularly. Complaints have been made but it is difficult for individual to fight this unhealthy trend unless the authorities take steps to minimize such personal intrusion. Looking forward, once the mobile devices can handle emails, web browser with 3G technology, it is foreseeable that there is a rise in m-commerce, and also it will come together with the criminal activities such as spamming, hacking of personal data from mobile devices. At this stage, the security of current wireless technology is a big issue with mobile devices.